Functional and phenotypic characterization of peripheral blood mononuclear cells from tuberculosis patients in Southern Thailand - Sone Oo, Pyae; Ongarj, Jomkwan; Sophonmanee, Ratchanon; Mohthong, Narisa; Suksan, Sahasawat; Saowaphong, Natapohn; Tanner, Rachel; Pinpathomrat, Nawamin (Frontiers in Immunology, 2025)
IntroductionTuberculosis (TB) remains a global health challenge, with active TB disease (ATB) and latent TB infection (LTBI) representing distinct immunological states. Understanding immune responses in these groups is critical for developing effective interventions. The complex nature of immune responses to Mycobacterium tuberculosis (M.tb) within and between different stages of TB, host evasion mechanisms of the bacterium, variable protection conferred by the BCG vaccine in adults, and lack of validated immune correlates of protection are among the key challenges to the successful control of TB.MethodsIn the present study, we conducted functional and phenotypic characterization of peripheral blood mononuclear cells (PBMCs) from a cohort in Southern Thailand. We compared immune responses in individuals with ATB, LTBI and healthy controls (HC) using flow cytometry (ATB n = 9, LTBI n = 11, HC n = 10) and the mycobacterial growth inhibition assay (MGIA) (ATB n = 13, LTBI n = 15, HC n = 15).ResultsMGIA revealed significantly enhanced control of BCG growth in the ATB group compared to LTBI and HC groups. Furthermore, NK cell frequency and TNF-α levels were significantly elevated in ATB compared to LTBI and HC groups, and CD4+ T cell TNF-α responses correlated with mycobacterial growth control.DiscussionThe findings from this study demonstrate differential immune responses across TB stages in this cohort, identify potential cellular markers for TB diagnosis and monitoring, and may guide vaccine strategies and host-directed therapies.